Orchestrated activation of mGluR5 and CB1 promotes neuroprotection. Issue 1 (December 2016) - Batista, Edleusa; Doria, Juliana; Ferreira-Vieira, Talita; Alves-Silva, Juliana; Ferguson, Stephen; Moreira, Fabricio; Ribeiro, Fabiola
Abstract The metabotropic glutamate receptor 5 (mGluR5) and the cannabinoid receptor 1 (CB1 ) exhibit a functional interaction, as CB1 regulates pre-synaptic glutamate release and mGluR5 activation increases endocannabinoid synthesis at the post-synaptic site. Since both mGluR5 and CB1 promote neuroprotection, we delineated experiments to investigate a possible link between CB1 and mGluR5 activation in the induction of neuroprotection using primary cultured corticostriatal neurons. We find that either the pharmacological blockade or the genetic ablation of either mGluR5 or CB1 can abrogate both CB1 - and mGluR5-mediated neuroprotection against glutamate insult. Interestingly, decreased glutamate release and diminished intracellular Ca2+ do not appear to play a role in CB1 and mGluR5-mediated neuroprotection. Rather, these two receptors work cooperatively to trigger the activation of cell signaling pathways to promote neuronal survival, which involves MEK/ERK1/2 and PI3K/AKT activation. Interestingly, although mGluR5 activation protects postsynaptic terminals and CB1 the presynaptic site, intact signaling of both receptors is required to effectively promote neuronal survival. In conclusion, mGluR5 and CB1 act in concert to activate neuroprotective cell signaling pathways and promote neuronal survival.